Optimal configuration for cascaded voltage source multilevel inverter based on series connection sub-multilevel inverter. Issue 1 (31st December 2016) - Thakre, Kishor; Barada Mohanty, Kanungo; Sagar Kommukuri, Vinaya; Chatterjee, Aditi
Abstract: In this study, a new configuration for cascaded voltage source multilevel inverter based on series connection of improved sub multilevel inverter module is presented. An algorithm is proposed to determine the magnitude of dc voltage source to generate a large number of output voltage levels with reduced device count. It is especially suitable for of renewable energy applications. To demonstrate the advantages of proposed configuration, the comparative analysis provided with other multilevel configurations in term of a number of switches, gate driver circuits and blocking voltage on switches. The comparison results confirm that the proposed configuration offers less number of components. Moreover, the magnitude of blocking voltage on switches and losses are lower in the proposed configuration. Multicarrier based sinusoidal pulse width modulation scheme is adopted for generating switching signals using dSPACE real-time controller. To validate the performance of proposed topology under steady state and dynamic condition are carried out using simulation on MATLAB/Simulink and experimental implementation.